Simulation of argon response and light detection in the DarkSide-50 dual phase TPC. (23rd October 2017) - Agnes, P.; Albuquerque, I.F.M.; Alexander, T.; Alton, A.K.; Asner, D.M.; Back, H.O.; Biery, K.; Bocci, V.; Bonfini, G.; Bonivento, W.; Bossa, M.; Bottino, B.; et al.
Abstract: A Geant4-based Monte Carlo package named G4DS has been developed to simulate the response of DarkSide-50, an experiment operating since 2013 at LNGS, designed to detect WIMP interactions in liquid argon. In the process of WIMP searches, DarkSide-50 has achieved two fundamental milestones: the rejection of electron recoil background with a power of\sim ∼ 10^7 7, using the pulse shape discrimination technique, and the measurement of the residual^{39} 39 Ar contamination in underground argon, \sim ∼ 3 orders of magnitude lower with respect to atmospheric argon. These results rely on the accurate simulation of the detector response to the liquid argon scintillation, its ionization, and electron-ion recombination processes. This work provides a complete overview of the DarkSide Monte Carlo and of its performance, with a particular focus on PARIS, the custom-made liquid argon response model.